2010
DOI: 10.1007/s00228-010-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian patients on generic antihypertensive drugs: a qualitative study of their own experiences

Abstract: ObjectivesThe aim of this study was to investigate experiences with and attitudes toward generic substitution in patients on antihypertensive medication.Materials and methodsStudy participants were 22 patients from pharmacies in Oslo who had taken brand antihypertensive products as well as substituted generic products. Five focus- group discussions were held.ResultsOnly a few participants claimed to take their medications as prescribed. Most reported low drug adherence before and after generic substitution. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 14 publications
4
39
0
4
Order By: Relevance
“…A number of studies conducted across several countries, including Japan, New Zealand, Bulgaria, Iraq, Malaysia, and Norway, explored medicine consumers' understanding of the differences between generic medicines and brand medicines, and many reported a lack of knowledge among a high proportion of participants. 34,36,38,39,41,61,62 For example, in Japan, only 71.1% stated that generic medicines and brand medicines have the same active ingredients. The majority (53.7%) of patients had no idea whether the inactive ingredients are the same or not, while 12.5% wrongly believed they are the same.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A number of studies conducted across several countries, including Japan, New Zealand, Bulgaria, Iraq, Malaysia, and Norway, explored medicine consumers' understanding of the differences between generic medicines and brand medicines, and many reported a lack of knowledge among a high proportion of participants. 34,36,38,39,41,61,62 For example, in Japan, only 71.1% stated that generic medicines and brand medicines have the same active ingredients. The majority (53.7%) of patients had no idea whether the inactive ingredients are the same or not, while 12.5% wrongly believed they are the same.…”
Section: Discussionmentioning
confidence: 97%
“…39 In Norway, most of the respondents were not aware what a generic medicine is and how it differs from the brand medicine, with only a few participants being aware that it is the same medicine (ie, the same active ingredient but possibly different excipients). 61 In Bulgaria, most participants were either in the "do not know" (46%) or "not sure" (43%) category when asked about the difference between brand and generic medicines. Further, nearly 75% of patients with chronic disease do not have enough information about the difference between generic and original medicines.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study by Hakonsen et al 23 with 174 outpatients in Oslo and Bergen in Norway revealed that 29% of patients were anxious when they started to use a substitute generic drug; 8% felt that the drug effect changed, and 15% reported having new or more side effects from the substitute. In pharmacies in Oslo, some of 22 patients who had already made use of antihypertensive generic and brand name drugs mentioned experiencing more side effects and weaker effects upon drug substitution 24 . In two studies conducted in Southern Brazil (2002 and 2011), it was observed that 70% of 3,182 respondents and 64.3% of 374 respondents considered the quality of generic drug products to be similar to brand name drug 16,25 .…”
Section: Generic Drugs Have An Overall Worse Quality Than Brand Name mentioning
confidence: 99%